Hybrid coronary artery revascularization: initial experience of a single centre. (9th March 2015) - Mikus, Elisa; Grattoni, Chiara; Fiore, Flavio; Conte, Massimiliano; Coppola, Roberto; Chierchia, Sergio; Bosi, Stefano; Jori, Maria Cristina; Castriota, Fausto; Del Giglio, Mauro
Abstract: Current guidelines recommend coronary bypass grafting (CABG) as the treatment of choice for patients with triple vessel and left main disease, although the growing use of drug-eluting stents (DES) has significantly reduced the rate of restenosis and extended the use of percutaneous coronary interventions (PCIs). Hybrid coronary revascularization (HCR) integrates the positive features of both PCI and CABG. We present preliminary results of a prospective study designed to verify the selection of candidates for treatment with hybrid approach. Between September 2011 and August 2014, 42 patients [( M = 37 (88.1%); mean age 68.6 ± 10.3 years, range 53–90] were selected to receive a complete (all lesions of main vessels treated) coronary revascularization with a hybrid approach at our Institution. Age-creatinine-ejection-fraction score was high (>1.277) in 16 (38%) patients, median 1.2 (0.77; 2.89). All patients underwent off-pump single-vessel revascularization (left internal thoracic artery to the left anterior descending coronary artery) using a left-anterior small thoracotomy and percutaneous coronary angioplasty. Eighteen patients (42.8%) underwent a simultaneous hybrid approach. Drug-eluting stents were used to treat 49 lesions, were also implanted 6 (7.6%) bioabsorbable stents. Procedural success was obtained in 41 (97.6%) patients. No conversion to full sternotomy and no blood transfusions were necessary during surgery. Median ventilation time was 7.7 (3–33) h and median hospital length of stay was 6 days (3–14). All patients were alive at discharge. Our early experience with HCR shows encouraging results. Randomized studies on a larger series with a longer follow-up are required.